2018
DOI: 10.2478/mgr-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Retail Format Competition: The Case of Grocery Discount Stores and Why They Haven’t Conquered the Chinese Market (Yet)

Abstract: The international expansion of the German discounters Aldi and Lidl in recent years has been a large success in grocery retailing. In China, the world’s largest grocery retail market, however, grocery discounters have not (yet) established a physical store presence. In 2017 Aldi Süd and Lidl for the first time entered a new market without the help of a physical store, implementing an online shop in China. As to the format’s future, significant disagreement amongst retail experts exists. This paper, which is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This confirms the fact that this store format has come under pressure due to current trends of consolidation and concentration plus a growing share of discounters that operate with extremely low margins. This has led to increased competition and declining market shares of independent/specialized retailers (Ahlert et al, 2010; Hardaker, 2018). Membership of a Top‐5 group is associated with higher profitability in France and amongst the set of larger firms in Sweden where the market is dominated by three large chains.…”
Section: Resultsmentioning
confidence: 99%
“…This confirms the fact that this store format has come under pressure due to current trends of consolidation and concentration plus a growing share of discounters that operate with extremely low margins. This has led to increased competition and declining market shares of independent/specialized retailers (Ahlert et al, 2010; Hardaker, 2018). Membership of a Top‐5 group is associated with higher profitability in France and amongst the set of larger firms in Sweden where the market is dominated by three large chains.…”
Section: Resultsmentioning
confidence: 99%
“…Grocery retailers frequently report major difficulties in realizing the potential offered by entering new markets, especially in regard to China (Siebers, 2011(Siebers, , 2017(Siebers, , 2018Zhang and Wei, 2015;Hardaker, 2018a). Due to considerable economic and sociocultural diversities across China, a high responsiveness to local circumstances, such as differing cultural tastes (Davis, 2013;Frank et al, 2014) and regulations must be complied with (Zhen, 2007).…”
Section: Ijrdm 497mentioning
confidence: 99%
“…As Colla (2003) reasons, mostly the discounter (such as Aldi, Lidl or Netto) reveal strong international presence, through operating a mono-format and a global concept, which is usually modified and adjusted only to a very small degree, as "Aldi usually educates its consumers, which is very unlikely to work in the Chinese market" (Interview VI, 2015). Hardaker (2018a) discussed in length that the discount format proves especially difficult to gain a foothold in the Chinese market. Reasons include the need for strong localization, the already low-price level as well as the lack of consumer acceptance regarding private brands, preventing major challenges for the discount format to prevail.…”
Section: Costco' Market Entry Into Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…At the international level, studies related to the impact of hard discount stores on the economy and consumers in Ecuador [1], their evolution in Germany [2], the defensive strategies of traditional businesses against hard discount formats in the Netherlands [3], the impossibility of conquering the Chinese market [4], among others; however, no studies were found evaluating the quality of the service of these formats.…”
Section: Introductionmentioning
confidence: 99%